Does Disassociation with a Majority Religion Influence Community Desirability? Evidence from Rural Utah. (April 2022) - Andre, Alex Nicholas; Sanders, Scott; Cope, Michael R.; Gibbs, Benjamin G.
This study examines how disassociation with a majority religion influences subjective perception of community desirability in rural communities. Current community literature shows that religious affiliation identification can influence community sentiment, while other studies suggest the possibility of either mixed or inconclusive results. To further clarify the relationship between religious affiliation and community desirability, we draw upon data from the 2017 Rural Utah Community Study. We find that even when accounting for the length of residence, age, and perception of local services, a resident's religious affiliation continues to be associated with community desirability. These findings have potential implications for understanding other communities with a large, singular religious presence.